Study the Performance of Nanozeolite NaA on CO2 Gas Uptake - Majeed, Najwa Saber; Majeed, Jwan Taher (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
The adsorption isotherms and kinetic uptakes of CO2 were measured. Adsorption isotherms were measured at two temperatures 309 K and 333 K and over a pressure range of 1 to 7 bar. Experimental data of CO2 adsorption isotherms were modeled using Langmuir, Freundlich and Temkin. Based on coefficient of correlation it was found that Langmuir isotherm model was well suited with the experimental data of CO2 adsorption isotherms.  In addition, Adsorption kinetic of CO2 mixture with N2 containing 10 % by volume CO2 and 90 % by volume N2 were determined in a temperature 36 °C and under the atmospheric pressure .When the flow rate was increased from 0.5 l/min to 2 l/min the time required for complete column saturation decreased. Also the effect of bed length on breakthrough curves was studied. The adsorption capacity increases by bed length increasing for adsorption of carbon dioxide.